Relationships among injury and disordered eating, menstrual dysfunction, and low bone mineral density in high school athletes: A prospective study - Rauh, M. J.; Nichols, J. F.; Barrack, M. T. (Journal of Athletic Training, 2010)
Context: Prior authors have reported associations among increased risk of injury and factors of the female athlete triad, as defined before the 2007 American College of Sports Medicine position stand, in collegiate and adult club sport populations. Little is known about this relationship in an adolescent competitive sports population.